Recurrent isolated abducens nerve palsy in a young woman – a case report - Żarnowski, Tomasz; Nowomiejska, Katarzyna; Zagórski, Zbigniew (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
We present a case of isolated unilateral abducens nerve palsy with multiple recurrences in a young woman. First episode occurred at the age of 12 with no apparent reason. The palsy resolved without other associated neurological signs or symptoms, neuro-imagining test were also normal. Since that time she had 6 episodes lasting 6-8 weeks with the average interval of 1 year and 4 months. Each episode was followed by a headache of the right hemisphere. The diagnosis of benign sixth nerve palsy is one of exclusion and may be made after the long period of observation and diagnostic procedures.